Propostas didáticas para o ensino do carste na Educação Básica - Joseane Biazini Mendes (2013)
Considering the importance that knowing the karst environment has for people who live in these areas and the actions whose aims are the teaching and learning of the karst at schools, the main objective of this work is to propose didactic activities which can lead to significant learning on karst subject. Proposed activities consider the students context, valuing prior knowledge, according to the Theory of Meaningful Learning (TML), follow the guidelines from the Brazilian National Education Parameters (PCN, in Portuguese) and are based on the correlation between the content covered in school discipline of geography related to the contents of the karst theme. To contextualize the research was chosen a city that is inserted in the karst region of the Upper São Francisco: Pains-MG. However, it is important to remark that the proposed activity can be applied to any school, wheter it is located in karst area or not. It is suficient that those who are interested follow the guidelines presented. To facilitate the research the following methodological approach was adopted: I) literature review to construct a theoretical framework giving subsidy to the preparation of this research; II) fieldwork carried out in the city of Pains-MG with interviews and questionnaires to further characterization, contextualization and understanding of the chosen area, and III) elaboration of didactic proposals to be used in the school classes. It is true that the teaching of thematic karst can enable the development of critical thinking environment by students and can be approached at anyin whatever stage the student is in the school system; however, it was observed from the literature review and the practical work the existing actions in this direction are still held timidly and punctual without support of suitable workbooks, which justifies the need of development of didactic-pedagogic proposals that could help the teachers work in the classroom. The two proposals were divided into steps that can be performed in an interconnected way or not. The steps are: i) introduction/contextualization and localization; ii) practical work; iii) discussion; and, iv) verification of learning. The first proposal is focused on middle school and the second proposal for the high school.